KEADILAN DALAM STUDI KASUS EKSEKUSI BIG MARY: REFLEKSI KRITIS ATAS ANTROPOSEN YANG BIJAK - Muhammad Zahrudin Afnan; Muhammad Ilham Ramadlan; Syafri Mushtofa (JURNAL ILMIAH NUSANTARA, 2025)
This article examines the execution of Big Mary, a circus elephant hanged in 1916, through Michel Foucault’s framework of biopolitics. Referencing the notion of “to make live and to let die,” it highlights how non-human bodies are subjected to modern power mechanisms that govern life for the sake of social and economic stability. Big Mary emerges not only as a victim of violence but also as a symbolic figure of how power disciplines deviation through elimination. In the Anthropocene context, her death reflects a deeper ecological and moral crisis, calling for a radical redefinition of justice across species. This paper proposes a new ethical paradigm that transcends anthropocentrism, advocating for an interspecies ecological politics grounded in empathy and shared dignity.